Bridge management - Yanev, Bojidar (Hoboken, NJ : Wiley, 2006)
A comprehensive, up-to-the-minute account of bridge management developments for researchers, designers, builders, administrators, and owners. Bridge Management draws on Bojidar Yanev's thirty years of research, teaching, and consulting as well as his management of 800 of New York City's 2,200 bridges. It offers an insider's view of the problems to be resolved in bridge management by civil and transportation engineers, budget and asset managers, abstract analysts, and hands-on field workers. The personal search of the author for solutions is juxtaposed with an overview of the dynamic interactions between bridge builders and the social and physical forces shaping the transportation infrastructure over the centuries. Bridge Management uniquely integrates the priorities, constraints, objectives, and tastes governing the domains of structural mechanics, economics, public administration, and field operations at both the project and network levels. It features: * A review of current bridge management vulnerabilities, objectives, tools, and products * Dozens of case studies illustrating the application of analytic models, and practical developments currently shaping the field * Unique chapters exploring the evolution of bridge design, construction, and maintenance, from the origins of deliberate planning to the current integrated lifecycle asset management models.
Chapter 1: Engineering and Management: The Dynamic Equilibrium -- Chapter 2: Objectives, Constraints, Needs, and Priorities -- Chapter 3: Failures -- Chapter 4: Vulnerabilities in Product and Process -- Chapter 5: Probability of Failure -- Chapter 6: System and Structure -- Chapter 7: Data Management -- Chapter 8: Inventory -- Chapter 9: Assessments: Conditions, Needs, and Resources -- Chapter 10: Structural Conditions -- Chapter 11: Needs -- Chapter 12: Decision Making -- Chapter 13: Tasks and Operations -- Chapter 14: Structural Inspection and Evaluation -- Chapter 15: New Technologies and BMS -- Chapter 16: Conclusion.
Includes bibliographical references (p. 511-531) and index.
1
Keywords: CEM; ITS; Bridges -- Maintenance and repair; Bridge failures -- Prevention; Bridges -- Inspection